Determination of Heavy Metals in the Fruit of Date Palm (Phoenix Dactylifera) From Different Locations in Tripoli, Libya - Abubaker Atrrog,; Aborawi Elgornazi,; Khadeja Samoe, (AlQalam Journal of Medical and Applied Sciences, 2025)
In this paper, we present results of the measurement of some heavy metals in 20 samples of Date palm (Phoenix dactylifera) fruit during the summer of 2024. Date palm is an important source of nutritional elements for people in Libya. This study aims to determine the concentration of Mn, Fe, Zn, Cd, Pb, and Cr. In Date palm fruit and we using Inductively Coupled Plasma-Optical Emission Spectrometry (5110 ICP-OES) the concentration Ranges in the Date palm samples were: 2-7, <0.002-110, <0.002, <0.002-5, <0.002-40, <0.002-2.5 ppm for manganese, iron, zinc, cadmium, lead and chromium, respectively. في هذه الورقة، نعرض نتائج قياس بعض المعادن الثقيلة في 20 عينة من ثمار نخيل التمر خلال صيف عام 2024. يُعدّ نخيل التمر مصدرًا هامًا للعناصر الغذائية في ليبيا. تهدف هذه الدراسة إلى تحديد تركيز كل من المنغنيز، والحديد، والزنك، والكادميوم، والرصاص، والكروم. في ثمار نخيل التمر، وباستخدام مطيافية الانبعاث الضوئي البلازمي المقترن حثيًا، كانت نطاقات التركيز في عينات نخيل التمر: 2-7، <0.002-110، <0.002، <0.002-5، <0.002-40، <0.002-2.5 جزء في المليون للمنغنيز، والحديد، والزنك، والكادميوم، والرصاص، والكروم، على التوالي